Graphics' design work: product / Aina Nazirah Junaidi - Junaidi, Aina Nazirah (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
'Kelupis Kedayan' by Ummu, which is a local food business established in 2023, is facing a challenge due to insufficient recognition. To address this issue, a comprehensive approach involving brand identity, effective advertising, and immersive multimedia are essential. The theme concept is "Modern Traditional." A collaboration between the corporate brand, advertising, and multimedia efforts is a must to ensure success and elevate the product's visibility for those visiting Sarawak.